Association between home and community-based services utilization and self-rated health among Chinese older adults with chronic diseases: evidence from the 2018 China Health and Retirement Longitudinal Study - Tingke Xu; Zishuo Huang; Bingzhen Li; Haojie Jin; Jiayun Zhang; Huiting Yang; Yucheng Huang; Xiangyang Zhang; Chun Chen (BMC, 2024)
Abstract Background As global aging intensifies, older adults with chronic diseases are of increasing concern. Home and community-based services (HCBSs) have been proven to promote self-rated health (SRH) in older adults, but no research explored the associations between the use of overall HCBSs, three different types of HCBSs (health care, daily care, and social support services) and SRH among older adults with chronic diseases. Consequently, this study applies a national publicly available database to examine these associations among older adults with chronic diseases. Methods 8,623 older adults with chronic diseases (≥ 60 years old) were included in this study. SRH was evaluated applying a concise question with a 1 − 5 scale. HCBSs utilization was assessed through the question, "What kind of HCBSs were used in the community?". Univariate general linear regression models aimed to compare the mean values of SRH in terms of HCBSs utilization in each group. This study is a cross-sectional study design and the relationship between HCBSs utilization and SRH was assessed by multilevel linear regression. Results The mean score for SRH among the respondents was 3.19, of whom 20.55% used one or more HCBSs, 19.47% utilized health care services, 2.44% utilized social support services, and only 0.55% utilized daily care services. The use of HCBSs was found to be linked to SRH among older adults with chronic diseases (β = 0.085, SE = 0.025, p < 0.001). SRH among older adults with chronic diseases was strongly linked to the use of health care and social support services (β = 0.068, SE = 0.025, p < 0.001; β = 0.239, SE = 0.063, p < 0.001, respectively). However, there was no significant association between the use of daily care services and SRH among older adults with chronic diseases. Conclusion This study revealed that HCBSs utilization was positively and significantly linked to SRH in Chinese older adults with chronic diseases. Furthermore, this study supposes the low utilization of social support and daily care services may be due to a mismatch between supply and demand. The government should offer the targeted HCBSs for older adults with chronic diseases according to their unique features to enhance their health status.